CURBING CORRUPTION THROUGH TERTIARY EDUCATION IN INDONESIA AND JAPAN (ANALYSIS OF LEGAL SYSTEM AND ISLAMIC PERSPECTIVE) - Abdurrachman Assegaf (Analisa: Journal of Social Science and Religion, 2017)
Corruption has become a global issue, whereas almost every country, whatever tough or slight it is, got to fight against it. It means that none of single country in the world is corruption free. This study analyzes anti-corruption policies and educational strategies enforced by Indonesian and Japanese Government. Data was collected through documentation and literature review, and to some extent, cultural behaviors of both countries were observed. This study used the theory of legal system by Lawrence M Friedman as an analysis method. The main research questions are: first, how are the Government’s policies enacted to eradicate corruption in Indonesia and Japan? Second, what educational strategies are implemented by both countries for combating corruption? Third, how Islamic perspective deals with anti-corruption practices? The research findings indicate several points: firstly, Indonesia has very complex social and cultural background if compared to Japan. Indeed Indonesia has some weaknesses such as weak of economic conditions, high levels of poverty, lack of political will, weak of cultural order, lack of honest and discipline attitudes, and lack of law enforcement. Indonesia’s anti-corruption policies enforced today is Act Number 31 of 1999, while Japan enacted several interrelated law compiled in Penal Codes (PC). Secondly, the implementation strategy for anti-corruption education in Indonesia is preventive, detective and repressive strategies. Meanwhile, Japan applies integrated strategies in social, political, economic, cultural, and education dimension. It is expected that the results of this study can contribute to the prevention and eradication of corruption in Indonesia more comprehensively, not only through legal means but education, especially higher education through internalization of moral and Islamic values of anti-corruption in all aspects of live.